Code-Switching in Translation: Linguistic Analysis of Multilingual Texts and their Translations - Alzain, Mohammed (International Journal of Linguistics, Literature and Translation, 2024)
This research explores the occurrence of code-switching in translation, focusing on instances where translators switch between languages within the same textual context, both intentionally and unintentionally. This study investigated the influence of linguistic factors such as language structure, semantic complexity, and intended communicative purpose on code-switching. The analysis employs qualitative methods to identify the strategies and challenges that translators face in managing code-switching. The study reveals that code-switching significantly contributes to semantic and cultural nuances in multilingual texts, emphasizing its critical role in translation accuracy and reader comprehension. The findings offer theoretical understanding and practical guidance for translation practice, enhancing the framework of multilingual translation studies. This research highlights the importance of code-switching in preserving the integrity and richness of multilingual communication in translated works. This study was conducted through the author’s personal efforts without any external funding or grants.